Organizing Audit of Business Continuity in Public Enterprises - Selishchev, S. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Quality of information on financial and economic situation at public enterprises and their capability to continue operation in the near future, supplied by the government bodies of economic control, has strong implications for the soundness of decisions on macroeconomic and financial policy, financial and economic performance of municipal institutions and entities with government participation. The main factors that affect the economic situation at public enterprises and may result in termination of their operation are studied, with emphasis on audit of public enterprises, based on the preliminary evaluated risk of termination of their operation. Practical recommendations on planning and programming of audit are given. The analysis of current practices allows for identifying the specific features of public enterprises, distinguishing them from private sector. These features necessitate modifications in auditor’s approaches to preliminary assessment of the internal risk of an enterprise in audit planning, especially when planning assessment of the risk of business termination. This approach will reduce the risk of non-detection, associated with the probability of business termination at a public enterprise, and optimize the time and resources required for audit.